2022
DOI: 10.1590/0100-3984.2021.0091-en
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension: an illustrated guide for the trainee radiologist

Abstract: Idiopathic intracranial hypertension is characterized by increased intracranial pressure, headache, and visual perturbations. Although the pathophysiology of idiopathic intracranial hypertension is obscure, several mechanisms have been proposed, such as increased cerebral blood volume, excessive cerebrospinal fluid volume (due to high production or impaired resorption), and inflammatory mechanisms as a likely cause of or contributor to impaired cerebrospinal fluid circulation. It predominantly affects women of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“… 10 , 19 , 25 However, most radiological findings of elevated ICP have high specificity but low sensitivity; flattening of the posterior sclera is, in isolation, the most specific finding. 26 Other MR imaging findings of elevated ICP include distention of the CSF sheath surrounding the optic nerve, nerve tortuosity, intraocular protrusion of the optic nerve head, and posterior flattening of the globe. 26 Our study showed that the coexistence of unilateral stenosis of the dominant TS sinus and contralateral TS hypoplasia is another radiological sign indicating elevated ICP, resulting in a large difference in volume between the bilateral sinuses (Vol difference ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 19 , 25 However, most radiological findings of elevated ICP have high specificity but low sensitivity; flattening of the posterior sclera is, in isolation, the most specific finding. 26 Other MR imaging findings of elevated ICP include distention of the CSF sheath surrounding the optic nerve, nerve tortuosity, intraocular protrusion of the optic nerve head, and posterior flattening of the globe. 26 Our study showed that the coexistence of unilateral stenosis of the dominant TS sinus and contralateral TS hypoplasia is another radiological sign indicating elevated ICP, resulting in a large difference in volume between the bilateral sinuses (Vol difference ).…”
Section: Discussionmentioning
confidence: 99%
“… 26 Other MR imaging findings of elevated ICP include distention of the CSF sheath surrounding the optic nerve, nerve tortuosity, intraocular protrusion of the optic nerve head, and posterior flattening of the globe. 26 Our study showed that the coexistence of unilateral stenosis of the dominant TS sinus and contralateral TS hypoplasia is another radiological sign indicating elevated ICP, resulting in a large difference in volume between the bilateral sinuses (Vol difference ). 10 In such cases, ICP may severely increase when the drainage of the dominant sinus, which is the only major conduit for intracranial venous drainage, is operatively impeded.…”
Section: Discussionmentioning
confidence: 99%
“…O diagnóstico e tratamento deve ser realizado de forma precoce para que assim possa atenuar as sequelas que são graves e possivelmente irreversíveis. O uso da RM com ARM venosa pode auxiliar na exclusão de uma trombose venosa cerebral nos pacientes com outros achados de HII (SAVASTANO et al, 2022).…”
Section: Considerações Finaisunclassified
“…Escavação da glândula pituitária até a "sela vazia" ( Os critérios diagnósticos para HII baseiam-se na clínica assim como nos achados da RM e na medida da pressão liquórica por punção lombar. Na maioria das vezes os achados radiológicos da HII têm alta especificidade e baixa sensibilidade (SAVASTANO et al, 2022).…”
unclassified